THE EVOLUTION AND METHODOLOGICAL INTEGRATION OF THE CONCEPT OF SUSTAINABLE USE (Marketing Journal, 2025)
The article analyzes the formation, theoretical evolution and methodological improvement of the concept of “sustainable use” based on a systemic approach. The aim of the study is to reinterpret the concept of sustainable use within the interrelation of eco logical, economic and institutional components, as well as to propose a model for its integration into practical management mechanisms. The research employs content analysis, historical -comparative and systemic synthesis methods, examining international do cuments (UNESCO, UNWTO, ICOMOS) and tracing the evolution of major paradigms since the adoption of the Brundtland Report in 1987. According to the results the concept of “sustainable use” unlike the notions of mere conservation or economic efficiency, represents a flexible management mechanism grounded in feedback relationships between human activities and natural systems. The conceptual model developed as a result of the study envisions ensuring a balance between ecological limits, social participation, and economic reinvestment in the process of utilizing heritage objects in tourism.
Keywords: sustainable use; systemic approach; content analysis; institutional mechanisms; ecological limits; heritage objects; sustainable tourism